1998
DOI: 10.1002/ana.410430519
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of preclinical and clinical lateonset Alzheimer's disease

Abstract: We report on the neuropathological examinations of a 74-year-old woman with Alzheimer's disease (AD) and of her 47-year-old nondemented daughter. The brain of the mother showed fully developed pathological changes of AD. By contrast, the brain of the daughter revealed only perineuronal deposition of diffuse amyloid in cerebral cortex and striking abnormalities of the endosomal-lysosomal system, without neurofibrillary, glial, or microglial changes. These observations suggest that amyloid deposition and endosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 19 publications
2
63
0
Order By: Relevance
“…A very different type of mechanism was implicated when it was recognized that neurofibrillary tangles comparable to those found in AD occur in young adults with Niemann-Pick's type C disease (17)(18)(19), a single gene mutation resulting in partial lysosomal dysfunction. Other postmortem analyses showed that lysosomal disturbances develop in AD vulnerable neurons in advance of AD pathologies (20)(21)(22)(23). Finally, studies using cultured slices from rat brain confirmed that experimentally induced lysosomal dysfunction generates hyperphosphorylated tau fragments (24,25) and other concomitants of AD (26).…”
mentioning
confidence: 81%
“…A very different type of mechanism was implicated when it was recognized that neurofibrillary tangles comparable to those found in AD occur in young adults with Niemann-Pick's type C disease (17)(18)(19), a single gene mutation resulting in partial lysosomal dysfunction. Other postmortem analyses showed that lysosomal disturbances develop in AD vulnerable neurons in advance of AD pathologies (20)(21)(22)(23). Finally, studies using cultured slices from rat brain confirmed that experimentally induced lysosomal dysfunction generates hyperphosphorylated tau fragments (24,25) and other concomitants of AD (26).…”
mentioning
confidence: 81%
“…Human Postmortem Brain Samples and Rat Tissues-Post mortem MTG samples of controls, AD, and HD (supplemental Table S1, A and B) subjects were obtained from the Department of Pathology of the Division of Neuropathology at Johns Hopkins University School of Medicine, where diagnoses were all confirmed by autopsy (37), and the samples were qualified for an exemption under 45 CFR 46.101 of the DHHS criteria. The RNA integrity of each sample was analyzed by the Agilent RNA 6000 Nano kit with Bioanalyzer (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 As a consequence, the long duration of preclinical AD dementia has been a major point of emphasis. [3][4][5] Although our direct knowledge of the preclinical sequences and interrelations of cognitive and pathologic events are limited, pathologic events are generally thought to begin much earlier than clinical ones.…”
mentioning
confidence: 99%